How Existing Conditions in Madrasah Tsanawiyah (MTs) Al Mursyidiyyah, South Tangerang City? Investigations with Using SWOT Analysis - Syamruddin Syamruddin; Mustika Mustika (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
This study aims to determine the current conditions at Madrasah Tsanawiyah (MTs) Al Mursyidiyyah, South Tangerang City. The method used in this study is mixed. While the data analysis techniques use SWOT Analysis, IFE Matrix Analysis, EFE Matrix Analysis, IE Matrix Analysis, SWOT Matrix, and SWOT Analysis Diagram. The results of the study show that the IFE Matrix has a score of 3.29 for strengths and weaknesses. Then, in the EFE Matrix, opportunities and threats have a score of 3.24. Based on the IE Matrix, the company's position in cell I shows that the appropriate strategy is to grow and develop (growth and build), which means this strategy is adjusted to the strengths of the company's internal side to take advantage of the right opportunities to gain benefits for the company. While in the SWOT Matrix using the SO, WO, ST, and WT formulas, twelve strategies are obtained. The results of the SWOT Analysis Diagram show that the company is in quadrant I, namely carrying out and supporting an aggressive strategy.